Correlation of Protein Contents and Milk Temperatures, with Milk Density of Friesian Holstein (FH) Cow in Ngablak District of Magelang Regency Central Java - Danes Suhendra; Mirza Aulia Rahman; Megawati Megawati (Journal of Livestock Science and Production, 2020)
Indicators of milk quality commonly used by the Milk Processing Industry (MPI) is the milk density (MD). Some factors that influence the milk density is milk protein in the form of casein and milk temperatures. This study aims to examine the correlation between protein content and milk temperature to milk density. The material used was 90 lactating FH cows in the II - III of lactation period and 2 – 3 of lactation months. The analysis used is simple linear correlation regression. The results showed that the increase in protein content caused an increase in the milk density by 73.48%. The decreased in temperature caused an increase in the milk density by 5.25%. Protein content and milk temperature to milk density had a significants correlation value (P 0.01). The overall calculation shows that there is a relationship between the protein content and milk temperature to milk density. Protein content with milk density, shows a very strong positive correlation. The milk temperature and the milk density shows a very strong negative correlation. The conclusion is that there is a positive relationship between protein content to milk density, and a negative relationship between milk temperature to milk density. The higher the protein content, the higher the milk density. The lower the milk temperature, the higher the milk density value. Keyword : milk, protein, temperature, density